The Effects of SEGUE Model on Health Communication Skills among Nursing Students - Chaichana, Jiranat; Konthiang, Kattiyaporn; Niramon , Poramaporn; Samerchua , Warodom (Journal of Nursing, Siam University, 2023)
This quasi-experimental study aimed to compare the health communication skill of nursing students in the pre and post-programmed groups, and to compare the health communication skill scores between the group receiving the SEGUE program and the group receiving regular program. The samples were 80 nursing students who are participated in the simulation base learning. Research instruments used were 1) SEGUE communication and 2) Thai Health Communication Assessment Tool (T-HCAT). The content validity was 0.95, the reliability was 0.99. Descriptive statistics and paired t-test were used in control and experimental groups compared between pre and post tests and t-test after the experiment. The results revealed that: 1) After participating in the program, the mean scores of health communication skill of the students who receiving the SEGUE program were significantly higher than before (p <.001). 2) After receiving the program, the mean scores of health communication skill of the students who receiving the SEGUE program were significantly higher than the control group (p <.001). It can be concluded that the effect of SEGUE program is important to help nursing students to gain the health communication skill and the SEGUE program can also be used to practicing the communication skill in other related fields.